Does Oil Price Volatility Drive Household Consumption Expenditures in Nigeria? - Jimoh Sina Ogede (Signifikan: Jurnal Ilmu Ekonomi, 2020)
This paper investigates whether volatilities in oil prices influence consumer household consumption expenditure from 1995 to 2019, a period described in the literature by the weakening effect of oil price volatility on macroeconomic factors. The Vector autoregressive model's findings suggest that the unexpected changes in oil prices significantly influence household consumption expenditure in Nigeria. A one standard deviation unexpected for a change in oil prices corresponds to a 28.31 percent increase in Nigeria's consumption expenditure. Moreover, the decomposition of the variance did not affect the sign and significance of the household relationship between oil price volatility and consumption expenditure. The paper offers that the extent to which dependence on oil continues depends on the magnitude to which Nigeria's economies can continue developing alternative energy sources and improving energy conservation.JEL classification: D15, Q43 How to Cite:Ogede, J. S. (2020). Does Oil Price Volatility Drive Household Consumption Expenditures in Nigeria? Signifikan: Jurnal Ilmu Ekonomi, 9(2), 257-268. https://doi.org/10.15408/sjie.v9i2.15498.